(untitled) (Journal of Fatima Jinnah Medical University, 2022)
Background: Diabetic retinopathy is a leading cause of preventable blindness in the world. Efficient and effective diagnosis and surveillance of diabetic retinopathy is of crucial importance to preserve the vision of patients. The FAZ (Foveal Avascular Zone) area is enlarged in patients of diabetic retinopathy. The purpose of this study was to evaluate the accuracy of OCT-A (Optical Coherence Tomography-Angiography) in delineating the FAZ area in cases of diabetic retinopathy and make a comparison with the findings of FFA (fundus fluorescein angiography) - the current gold standard. Subjects and methods: This was a comparative analytical study carried out at a tertiary care hospital in Lahore, Pakistan. A series of 50 patients, 30 males and 20 females with a mean age of 40 years were selected from the hospital outpatient department with history of five years of diabetic retinopathy. They were classified according to the ETDRS classification system into NPDR and PDR groups. The patients were booked for OCT-A, the scans were then observed for findings with a specific focus on the area of the FAZ at the level of the superficial capillary plexus. The patients then underwent same day FFA the current gold standard modality for diabetic retinopathy, thereafter a comparison between the mean area of the FAZ in both the modalities was made & documented. Data was analyzed using SPSS version 25.0. Results: The FAZ was easily distinguished by both FFA and OCT-A. The mean FAZ area was 0.62 mm2 on FFA and 0.69 mm2 on OCT-A. There was a statistically significant difference between the two means (p=0.002). Both the modalities had a Sensitivity of 100% at 0.44 and 0.48 cut-offs. OCT-A had a specificity of 91.9% and FFA had a Specificity of 89.2%. Conclusions: OCT-A proved to be an effective and accurate modality in delineating the FAZ area and detecting macular ischemia in patients of diabetic retinopathy in comparison to the current Gold-Standard FFA.